Interaction between habits as action sequences and goal-directed behavior under time pressure - Frölich, Sascha; Esmeyer, Marlon; Endrass, Tanja; Smolka, Michael N.; Kiebel, Stefan J. (Frontiers in Neuroscience, 2023)
Human behaviour consists in large parts of action sequences that are often repeated in mostly the same way. Through extensive repetition, sequential responses become automatic or habitual, but our environment often confronts us with events to which we have to react flexibly and in a goal-directed manner. To assess how implicitly learned action sequences interfere with goal-directed control, we developed a novel behavioural paradigm in which we combined action sequence learning through repetition with a goal-directed task component. So-called dual-target trials require the goal-directed selection of the response with the highest reward-probability in a fast succession of trials with short response deadlines. Importantly, the response primed by the learned action sequence is sometimes different from that required by the goal-directed task. As expected, we found that participants learned the action sequence through repetition, as evidenced by reduced reaction times and error rates, while still acting in a goal-directed manner in dual target trials. Specifically, we found that the learned action sequence biased choices in the goal-directed task towards the sequential response, and this effect was more pronounced the better individuals had learned the sequence. Our novel task may help shed light on the acquisition of automatic behavioural patterns and habits through extensive repetition, allows to assess positive features of habitual behaviour (e.g. increased response speed and reduced error rates), and importantly also the interaction of habitual and goal-directed behaviours under time pressure.